2015
DOI: 10.1542/peds.2014-1532
|View full text |Cite
|
Sign up to set email alerts
|

Early Weight Loss Nomograms for Exclusively Breastfed Newborns

Abstract: BACKGROUND: The majority of newborns are exclusively breastfed during the birth hospitalization, and weight loss is nearly universal for these neonates. The amount of weight lost varies substantially among newborns with higher amounts of weight loss increasing risk for morbidity. No hour-by-hour newborn weight loss nomogram exists to assist in early identification of those on a trajectory for adverse outcomes.METHODS: For 161 471 term, singleton neonates born at $36 weeks' gestation at Northern California Kais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
156
3
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(170 citation statements)
references
References 32 publications
(20 reference statements)
6
156
3
5
Order By: Relevance
“…For example, these investigators found that the nadir in weight for neonates at the 50th percentile on their nomograms occurred at ∼60 hours of age. 3 This is similar to data from MacDonald et al and Marchini and Stock, who reported that the nadir occurred on the third day of life. 4,5 The nomogram data for weight loss in neonates born by cesarean delivery are jarring, with Flaherman et al reporting that 25% of these newborns have a weight loss $10%.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…For example, these investigators found that the nadir in weight for neonates at the 50th percentile on their nomograms occurred at ∼60 hours of age. 3 This is similar to data from MacDonald et al and Marchini and Stock, who reported that the nadir occurred on the third day of life. 4,5 The nomogram data for weight loss in neonates born by cesarean delivery are jarring, with Flaherman et al reporting that 25% of these newborns have a weight loss $10%.…”
supporting
confidence: 90%
“…3 Using a large database and an elegant methodology, Dr Flaherman and her colleagues have constructed nomograms that describe weight loss in breastfed infants during the first few days of life. With the nomograms, clinicians can plot the percent weight loss for a neonate at a specific age and determine, with precision, whether this percentage is normal for a breastfed newborn (eg, at the 50th percentile) or excessive (eg, $95th percentile).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the evaluation of other variables associated with weight loss and breastfeeding difficulties13 , 20 was not performed, which can be seen as a study limitation. Also, the longer duration of hospital length of stay after a cesarean delivery when compared to vaginal delivery would predispose to the observation of weight loss nadir in this first group 21. However, this effect was suppressed by adjusting the regression analysis for the length of stay in hours.…”
Section: Discussionmentioning
confidence: 94%
“…, 5 , 11 , 15 , 20 - 22 Thus, 2.45 to 25%21 of newborns lose more than 10% of weight according to studies with different types of feeding. The absence of newborns with weight loss>10% has also been described 3…”
Section: Discussionmentioning
confidence: 99%